Effect of Layers on Delamination and Tensile Strength of Woven Fiber Composites with Polyester Matrix - Fajar Paundra; Danang Istanto; Eko Pujiyulianto; Muhamad Fatikul Arif; Sri Hastuti (Jurnal Teknik Mesin (Sinta 3), 2024)
A composite is a combination of 2 or more different materials. The composite joining process can use adhesives or mechanically by making holes. During the process of making holes in the composite, it can cause delamination in the composite. Delamination and layer thickness greatly influence the strength of hollow composite joints. This research aims to determine the effect of delamination factors and the number of layers on the tensile strength value of the composite. The materials used in this research are polyester resin and woven glass fiber. The method used is vacuum bagging with variations in the number of layers, namely 3 layers, 4 layers, 5 layers, and 6 layers. Tensile testing refers to ASTM D638 standards. Specimens that have been cut according to standards will then be perforated in the center with a hole diameter of 4 mm using a milling machine. The highest tensile strength value was obtained in the 6-layer variation of 237.448 MPa and the lowest value was obtained in the 3-layer variation of 186.221 MPa. The delamination value greatly influences the tensile strength of the composite, where the more layers, the delamination value will decrease and increase the tensile strength of the composite.